2018
DOI: 10.1029/2017gb005840
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in Active‐Layer Tundra Soils of Alaska: Concentrations, Pools, Origins, and Spatial Distribution

Abstract: Tundra soils serve as major sources of mercury (Hg) input to the Arctic Ocean via river runoff and coastal erosion; yet little information is available on tundra soil Hg concentrations, pool sizes, origins, and dynamics. We present a detailed investigation of Hg in the active layer (upper ~100 cm subject to seasonal thaw) of tundra soils across 11 sites in Alaska. Soil Hg concentrations in organic horizons (151 ± 7 μg/kg) were in the upper range of temperate soil organic horizons, and concentrations in mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
78
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 100 publications
(202 reference statements)
9
78
1
Order By: Relevance
“…In the present study, even though Hg concentrations and SOM were generally much lower than the Alaskan tundra soils there was a strong linear relationship between soil (%) C and Hg with a slope (ratio) of 5.9, mid-way between values reported by Olson et al (2018). This relationship is explained by foliar uptake of Hg 0 , which then enters soils through litter fall over millennia (Olson et al, 2018), and is consistent with spatial patterns in soil Hg observed in this study. Friedli et al (2007) similarly reported that most (95%) of the Hg in upland boreal forests in Saskatchewan is associated with organic matter but highlighted concerns over potential Hg emissions following forest fires that may increase in frequency and severity with climate change.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…In the present study, even though Hg concentrations and SOM were generally much lower than the Alaskan tundra soils there was a strong linear relationship between soil (%) C and Hg with a slope (ratio) of 5.9, mid-way between values reported by Olson et al (2018). This relationship is explained by foliar uptake of Hg 0 , which then enters soils through litter fall over millennia (Olson et al, 2018), and is consistent with spatial patterns in soil Hg observed in this study. Friedli et al (2007) similarly reported that most (95%) of the Hg in upland boreal forests in Saskatchewan is associated with organic matter but highlighted concerns over potential Hg emissions following forest fires that may increase in frequency and severity with climate change.…”
Section: Discussioncontrasting
confidence: 49%
“…While several studies have shown that a number of metals including V and Hg are released to the atmosphere as a result of industrial processes in the Athabasca Oil Sands Region, metal levels in lichen and moss tissue decrease exponentially with distance from the industrial center (Addison and Puckett, 1980; Kirk et al, 2014; Shotyk et al, 2014) and there is no evidence that oil sands emissions have led to elevated levels of these metals in surface soils in Saskatchewan. Instead, recent studies in tundra soils in Alaska have shown that Hg pools in soils are high (mean concentrations of Hg in upper mineral soil 110 ng g −1 ) and closely linked to soil C (average 12% C in the A horizon), with a mean Hg (ng g −1 ) to C (%) ratio of 4.0 in the O horizon and 9.2 in the A horizon (Olson et al, 2018). In the present study, even though Hg concentrations and SOM were generally much lower than the Alaskan tundra soils there was a strong linear relationship between soil (%) C and Hg with a slope (ratio) of 5.9, mid‐way between values reported by Olson et al (2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the manuscript, the authors refer to northern soil Hg pools calculated by Schuster et al (2018) et Olson et al (2018) for the upper 1 m: 755 Gg and 184 Gg, respectively. Olson et al (2018) actually showed that Arctic tundra soils store 184 Gg of Hg while boreal soils store additional 224 Gg. The authors therefore reported a pool of 408 Gg of Hg for northern tundra and boreal soils.…”
mentioning
confidence: 99%